IMPLEMENTASI PROGRAM INOVASI PEMBANGUNAN DAN PEMBERDAYAAN KEWILAYAHAN (PIPPK) DI KELURAHAN TAMANSARI KECAMATAN BANDUNG WETAN KOTA BANDUNG TAHUN 2019 - Ayu Khoirunisa; Engkus Engkus; Nanang Suparman; Gian Rabbani (Sekolah Tinggi Pariwisata Mataram, 2021)
Tamansari Village which is located in the Bandung Wetan District is one of the areas that has implemented the Regional Development and Empowerment Innovation Program (PIPPK), researchers attempt to describe how to implement the Regional Development Innovation and Empowerment Program (PIPPK) policy in the Tamansari village area in 2019 and explain in depth the situation that occurred, how the information conveyed by the local government to the community related to the PIPPK policy, understanding the resources of the content of the policy itself, how the support and participation of the community, as well as the distribution of potential related to coordination between the government and the community in the activities of the Development Innovation Program and Regional Empowerment (PIPPK) which can affect the implementation of the process of empowerment and development activities in the Tamansari Village area. With a qualitative approach that is described descriptively guided by the theory of Jan Merse, where every phenomenon that occurs in PIPPK activities is certainly influenced by the weakness of Human Resources (HR) as actors, implementing PIPPK, in understanding and implementing PIPPK policies in development. and community empowerment.